“More Than Professional Skills:” Student Perspectives on Higher Education’s Purpose - Trinidad, Jose Eos R (Archīum Ateneo, 2021)
Universities have multiple functions of teaching, research, community development, and social impact, with the teaching function often thought of as just equipping students with professional knowledge and skills. However, the purpose of students’ higher education may span more than just career preparation, and this knowledge of other purposes could influence how universities can provide opportunities for attaining these goals. Through in-depth interviews of undergraduate students, we find three core purposes of higher education: It qualifies students to receive the necessary knowledge, skills, and certification for professional involvement; it socialises them to broader perspectives of society and others; and it makes them subjects who think for themselves and clarify what values they hold. Although most students still put primacy on the qualification purpose of higher education, the integration of these three purposes will have an impact on how education quality may be more clearly understood, better assessed, and more intentionally pursued.